Modified lithium nickel manganese oxide positive electrode material, preparation method thereof and battery

By forming a uniform, continuous and dense cladding layer on the surface of the nickel-manganate positive electrode material, the problem of the decrease in capacity and short cycle life of the nickel-manganate positive electrode material when circulating under high pressure conditions is solved, and the capacity and circulation performance of the battery are significantly improved.

CN119725475AActive Publication Date: 2025-03-28YIBIN LIBODE NEW MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411935197.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

When the nickel-lithium manganate positive electrode material is circulated under high pressure conditions, the surface contact with the electrolyte and the dissolution of the metal manganese ions leads to a short cycle life and a decrease in capacity.

Method used

By atomizing the coater nanodispersion liquid dispersed by sand mill into the fluidized bed with airflow, mixing it with the Ni-Manganate Lithium Manganate positive electrode material in the fluidized bed, and sintering it to form a uniform, continuous, dense and thicker cladding layer.

Benefits of technology

Effectively block the dissolution of Mn3+, avoid the electrolyte from directly contacting the positive electrode surface, and improve the battery capacity and circulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725475A_ABST
    Figure CN119725475A_ABST
Patent Text Reader

Abstract

The invention discloses a modified lithium nickel manganese oxide positive electrode material, a preparation method thereof and a battery, and belongs to the technical field of battery materials. The preparation method of the modified lithium nickel manganese oxide positive electrode material comprises the following steps: spraying a coating agent nano dispersion liquid dispersed by sanding into a fluidized bed by using airflow atomization, mixing with a lithium nickel manganese oxide positive electrode material in a flowing state, and sintering, the particle size of the coating agent does not exceed 100nm, and the dosage of the coating agent does not exceed 10wt% of the lithium nickel manganese oxide positive electrode material; the thickness of the coating layer is not less than 10nm; the gas for atomizing the coating agent nano dispersion liquid is air, and the flow of the gas is 20 L / min-50 L / min; the temperature of the hot air enabling the lithium nickel manganese oxide positive electrode material to be in a flowing state is 100-130 DEG C, and the air inflow is 0.2 m < 3 > / min-0. 5m < 3 > / min. According to the method, a uniform, continuous and compact thick coating layer can be formed on the surface of the lithium nickel manganese oxide positive electrode material, and the capacity and the cycle performance of the positive electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a modified lithium nickel manganese oxide positive electrode material and a preparation method thereof and a battery. Background Art

[0002] Lithium nickel manganese oxide positive electrode materials (LNMO) generally have the problem of rapid capacity decline resulting in short cycle life. The main reasons include: when cycling under high-voltage conditions, the contact between the surface of the lithium nickel manganese oxide positive electrode material and the dissolution of metal manganese ions will seriously affect the material's cycle and rate performance; in addition, the surface of the lithium nickel manganese oxide positive electrode material is highly active and easily reacts with the electrolyte, which reduces the cycle performance and safety.

[0003] At present, coating is often used on the surface of lithium nickel manganese oxide positive electrode materials to improve the above problems, but the existing coating method has limited effect on cycle improvement and the corresponding capacity of the material is relatively low.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a modified nickel manganese oxide lithium positive electrode material and a preparation method and a battery thereof, so as to solve or improve the above technical problems.

[0006] The present invention can be implemented like this:

[0007] In a first aspect, the present invention provides a method for preparing a modified lithium nickel manganese oxide positive electrode material, comprising the following steps:

[0008] The coating agent nano-dispersion liquid dispersed by sand milling is sprayed into a fluidized bed by air flow atomization, mixed with the lithium nickel manganese oxide positive electrode material in a flowing state in the fluidized bed, and sintered to obtain a modified lithium nickel manganese oxide positive electrode material containing a coating layer;

[0009] The particle size of the coating agent in the coating agent nano-dispersion liquid is not more than 100 nm; the amount of the coating agent is not more than 10 wt% of the lithium nickel manganese oxide positive electrode material; the thickness of the coating layer is not less than 10 nm;

[0010] The gas used for atomizing the coating agent nano-dispersion liquid is air, and the air flow rate is 20L / min to 50L / min; hot air is introduced into the fluidized bed to make the lithium nickel manganese oxide positive electrode material flow; the temperature of the hot air is 100°C to 130°C; the air intake volume of the hot air is 0.2m 3 / min~0.5m 3 / min.

[0011] In an optional embodiment, the coating layer has a thickness of 10 nm to 20 nm;

[0012] Alternatively, the amount of the coating agent is 1 wt% to 5 wt% of the lithium nickel manganese oxide positive electrode material.

[0013] In an alternative embodiment, the coating agent includes at least one of yttrium oxide, tungsten oxide, and tantalum oxide.

[0014] In an alternative embodiment, the concentration of the capping agent in the capping agent nanodispersion does not exceed 10 wt %.

[0015] In an optional embodiment, the sintering temperature is 500° C. to 800° C., and the sintering time is 6 h to 10 h.

[0016] In an optional embodiment, the preparation of the lithium nickel manganese oxide positive electrode material comprises: mixing a lithium nickel manganese oxide positive electrode material precursor with a lithium source and then calcining;

[0017] Among them, the chemical formula of the lithium nickel manganese oxide positive electrode material precursor is Ni x Mn y (OH)2, 0.2≤x≤0.3, y=1-x;

[0018] The lithium source includes lithium carbonate;

[0019] The ratio of the molar amount of Li in the lithium source to the total molar amount of Ni and Mn in the lithium nickel manganese oxide positive electrode material precursor is 0.5:1 to 0.55:1.

[0020] In an optional embodiment, the lithium nickel manganese oxide positive electrode material precursor is mixed with a lithium source and a dopant and then calcined;

[0021] The dopant includes at least one of SrCO3, Sb2O3 and Nb2O5, and the amount of each dopant is 0.1wt% to 2wt% of the lithium nickel manganese oxide positive electrode material precursor.

[0022] In an optional embodiment, the calcination temperature is 900° C. to 1100° C., and the calcination time is 8 h to 15 h.

[0023] In a second aspect, the present invention provides a modified lithium nickel manganese oxide positive electrode material, which is prepared by the preparation method of any one of the aforementioned embodiments.

[0024] In a third aspect, the present invention provides a battery, wherein the raw materials for preparing the battery include the modified lithium nickel manganese oxide positive electrode material of the aforementioned embodiment.

[0025] The beneficial effects of the present invention include:

[0026] The present invention sprays the coating agent nano-dispersion liquid dispersed by sand milling into a fluidized bed by air flow atomization, mixes with the lithium nickel manganese oxide positive electrode material in a flowing state in the fluidized bed, sinters, and controls the temperature and air intake of hot air, the amount of the coating agent nano-dispersion liquid, and the air flow rate of the atomized coating agent nano-dispersion liquid, so as to form a uniform, continuous, dense and thick coating layer on the surface of the lithium nickel manganese oxide positive electrode material, thereby facilitating the isolation of Mn 3+ The dissolution of the lithium nickel manganese oxide positive electrode material is prevented, thereby preventing the electrolyte from directly contacting the positive electrode surface, thereby preventing the electrolyte from corroding the positive electrode material surface during the cycle process, and improving the capacity and cycle performance of the battery prepared from the lithium nickel manganese oxide positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 This is a SEM image of the modified lithium nickel manganese oxide positive electrode material prepared in Example 1;

[0029] Figure 2 This is a SEM image of the modified lithium nickel manganese oxide positive electrode material prepared in Example 2;

[0030] Figure 3 This is a SEM image of the modified lithium nickel manganese oxide positive electrode material prepared in Comparative Example 1;

[0031] Figure 4 It is the XPS graph of the modified lithium nickel manganese oxide positive electrode material prepared in Examples 1-2 and Comparative Examples 1 and 3. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0033] The modified lithium nickel manganese oxide positive electrode material, preparation method thereof and battery provided by the present invention are described in detail below.

[0034] After research, the inventor proposed that the reason why the existing coating methods have limited effect on improving the cycle of lithium nickel manganese oxide positive electrode materials is that most of the existing methods use a coating agent to mechanically mix with the lithium nickel manganese oxide positive electrode material, and then sinter at high temperature to achieve the coating effect. For nano-metal oxide particle coating agents, the coating usually presents an island shape and non-uniform distribution, and it is difficult to obtain a thicker coating layer. In other words, it is difficult to obtain a uniform coating layer by mechanical mixing, and it is difficult to obtain a full coating effect on the surface of the lithium nickel manganese oxide positive electrode material. In addition, the coating layer obtained by mechanical mixing is easy to be deformed during the cycle due to the deformation of the lithium nickel manganese oxide positive electrode material and Li + The disembedding and falling off will reduce the cycle performance and safety.

[0035] The positive electrode material of lithium nickel manganese oxide is different from other positive electrode materials. 3+ The dissolution of Mn is one of the main reasons for cycle attenuation. In order to effectively improve the cycle performance of lithium nickel manganese oxide positive electrode materials by coating, it is necessary to coat the surface of the lithium nickel manganese oxide positive electrode material with a continuous, dense and uniform coating layer to reduce the direct contact between the surface of the lithium nickel manganese oxide positive electrode material and the electrolyte, slowing down the Mn 3+ dissolution, thereby improving the cycle performance of lithium nickel manganese oxide positive electrode materials.

[0036] Based on this, the present invention provides a method for preparing a modified lithium nickel manganese oxide positive electrode material, comprising the following steps: spraying a coating agent nano-dispersion liquid dispersed by sand grinding into a fluidized bed by air flow atomization, mixing it with the lithium nickel manganese oxide positive electrode material in a flowing state in the fluidized bed, and sintering to obtain a modified lithium nickel manganese oxide positive electrode material containing a coating layer.

[0037] Wherein, the coating agent nano-dispersion liquid is obtained by mixing the coating agent with water. Wherein, the coating agent includes at least one of yttrium oxide, tungsten oxide and tantalum oxide. The concentration of the coating agent in the coating agent nano-dispersion liquid does not exceed 10wt%, for example, it can be 10wt%, 9wt%, 8wt%, 7wt%, 6wt%, 5wt%, 4wt%, 3wt%, 2wt%, 1wt% or 0.5wt%, etc., or it can be other values ​​within the range of not more than 10wt%. In some preferred embodiments, the concentration of the coating agent in the coating agent nano-dispersion liquid is 1wt% to 10wt%.

[0038] The particle size of the coating agent in the coating agent nano dispersion after sand milling dispersion is no more than 100nm, for example, it can be 100nm, 90nm, 80nm, 70nm, 60nm, 50nm, 40nm, 30nm, 20nm or 10nm, etc., or it can be other values ​​within the scope of no more than 100nm. If the particle size of the coating agent in the coating agent nano dispersion after sand milling dispersion exceeds 100nm, it is not conducive to coating density and uniformity, and affects the effect of improving cycle performance.

[0039] The amount of the coating agent does not exceed 10wt% of the lithium nickel manganese oxide positive electrode material, for example, it can be 10wt%, 9wt%, 8wt%, 7wt%, 6wt%, 5wt%, 4wt%, 3wt%, 2wt%, 1wt% or 0.5wt%, etc., or it can be other values ​​within the range of not more than 10wt%. In some preferred embodiments, the amount of the coating agent is 1wt% to 5wt% of the lithium nickel manganese oxide positive electrode material. If the amount of the coating agent exceeds 10wt% of the lithium nickel manganese oxide positive electrode material, it will affect the normal deintercalation of lithium ions, resulting in a significant decrease in the capacity of the modified lithium nickel manganese oxide positive electrode material.

[0040] The thickness of the coating layer is not less than 10 nm, for example, it can be 10 nm, 20 nm, 30 nm or 40 nm. In some preferred embodiments, the thickness of the coating layer is 10 nm to 20 nm. By setting the thickness of the coating layer to 10 nm to 20 nm, it is possible to better avoid the dissolution of manganese ions and the direct contact of the electrolyte with the positive electrode material. In addition, it is also possible to avoid the insufficient capacity due to the excessive thickness of the coating layer, which affects the normal deintercalation of lithium ions in the lithium nickel manganese oxide (LNMO) body.

[0041] In the present invention, the gas used for atomizing the coating agent nano-dispersion liquid is air, and the flow rate of the air is 20L / min to 50L / min, such as 20L / min, 25L / min, 30L / min, 35L / min, 40L / min, 45L / min or 50L / min, etc., and can also be other values ​​within the range of 20L / min to 50L / min. If the flow rate of the air is too low, it is difficult to atomize the coating agent nano-dispersion liquid, and the coating agent nano-dispersion liquid will form droplets, resulting in poor coating effect; if the flow rate of the air is too high, it is not conducive to maintaining the integrity of the LNMO body morphology, and it is easy to form defects and form micropowders on the surface, which deteriorates the material properties.

[0042] In the present invention, hot air is introduced into the fluidized bed to make the lithium nickel manganese oxide positive electrode material flow. The hot air can be introduced from the bottom of the fluidized bed.

[0043] The temperature of the hot air can be 100° C. to 130° C., such as 100° C., 105° C., 110° C., 115° C., 120° C., 125° C. or 130° C., or other values ​​within the range of 100° C. to 130° C. By using the hot air at the above temperature, part of the water in the coating agent nano-dispersion can be evaporated when in contact with the coating agent nano-dispersion, thereby avoiding the situation where too much water causes the material to agglomerate and causes uneven coating.

[0044] The hot air intake can be 0.2m 3 / min~0.5m 3 / min, such as 0.2m3 / min, 0.25m 3 / min、0.3m 3 / min, 0.35m 3 / min、0.4m 3 / min, 0.45m 3 / min or 0.5m 3 / min, etc., can also be 0.2m 3 / min~0.5m 3 Other values ​​within the range of / min.

[0045] By setting the temperature and air intake of the hot air within the above range, combined with the amount of the coating agent nanodispersion and the air flow rate of the atomized coating agent nanodispersion, it is beneficial for the coating agent to form a uniform, continuous, complete and dense coating on the surface of the lithium nickel manganese oxide positive electrode material.

[0046] In some optional embodiments, the sintering temperature may be 500°C to 800°C, such as 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, or other values ​​within the range of 500°C to 800°C.

[0047] The sintering time may be 6 h to 10 h, such as 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h or 10 h, etc., or other values ​​within the range of 6 h to 10 h.

[0048] The above coating process is a continuous spray coating process.

[0049] In the present invention, a uniform and thick dense full coating is formed on the surface of the lithium nickel manganese oxide positive electrode material to effectively block the Mn 3+ The dissolution of the electrolyte avoids direct contact with the positive electrode surface, thereby preventing the electrolyte from corroding the surface of the positive electrode material during the cycle.

[0050] In some optional embodiments, the preparation of the lithium nickel manganese oxide positive electrode material may include: mixing a lithium nickel manganese oxide positive electrode material precursor with a lithium source and then calcining;

[0051] Among them, the chemical formula of the lithium nickel manganese oxide positive electrode material precursor is Ni x Mn y (OH)2, 0.2≤x≤0.3, y=1-x.

[0052] The lithium source includes lithium carbonate, and the ratio of the molar amount of Li in the lithium source to the total molar amount of Ni and Mn in the lithium nickel manganese oxide positive electrode material precursor is 0.5:1 to 0.55:1.

[0053] In other embodiments, the lithium nickel manganese oxide positive electrode material precursor may be mixed with a lithium source and a dopant and then calcined. The dopant includes at least one of SrCO3, Sb2O3 and Nb2O5, and the amount of each dopant is 0.1wt% to 2wt% of the lithium nickel manganese oxide positive electrode material precursor, such as 0.1wt%, 0.5wt%, 1wt%, 1.5wt% or 2wt%, and may also be other values ​​within the range of 0.1wt% to 2wt%.

[0054] In some optional embodiments, the calcination temperature may be 900°C to 1100°C, such as 900°C, 950°C, 1000°C, 1050°C or 1100°C, or other values ​​within the range of 900°C to 1100°C. The calcination time may be 8h to 15h, such as 8h, 9h, 10h, 11h, 12h, 13h, 14h or 15h, or other values ​​within the range of 8h to 15h.

[0055] It should be noted that the lithium nickel manganese oxide positive electrode material precursor can also be purchased directly. In addition, other conditions in the preparation process of the lithium nickel manganese oxide positive electrode material precursor can refer to the relevant existing technology, and no further elaboration or limitation is made here.

[0056] Correspondingly, the present invention also provides a modified lithium nickel manganese oxide positive electrode material, which is prepared by the above preparation method.

[0057] The modified lithium nickel manganese oxide positive electrode material comprises a lithium nickel manganese oxide positive electrode material and a coating layer coated on the surface of the lithium nickel manganese oxide positive electrode material.

[0058] In addition, the present invention also provides a battery, the raw materials for preparing the battery include the modified lithium nickel manganese oxide positive electrode material, and the battery has a high capacity and cycle retention rate.

[0059] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0060] Example 1

[0061] This embodiment provides a modified lithium nickel manganese oxide positive electrode material, and the preparation method thereof includes:

[0062] S1: preparing lithium nickel manganese oxide positive electrode material.

[0063] 1 kg of Ni 0.25 Mn 0.75 The (OH)2 precursor was mixed with 207g of lithium carbonate and dopants (5g of SrCO3, 5g of Sb2O3 and 5g of Nb2O5) and then calcined to obtain the lithium nickel manganese oxide positive electrode material Li 0.5 Ni 0.25 Mn 0.75O2, after crushing, pass through 400 mesh sieve for later use.

[0064] The heating rate during the calcination process was 3°C / min, the temperature was raised to 980°C and kept for 10 hours, and the calcination was carried out in an air atmosphere.

[0065] S2: coating the lithium nickel manganese oxide positive electrode material.

[0066] 500 g of yttrium oxide nano-dispersion dispersed by sand milling was sprayed into the fluidized bed by air flow atomization, mixed with 1 kg of lithium nickel manganese oxide positive electrode material in a flowing state in the fluidized bed, and sintered to obtain a modified lithium nickel manganese oxide positive electrode material.

[0067] The concentration of the yttrium oxide nano-dispersion liquid is 10wt%, and the particle size of the yttrium oxide in the yttrium oxide nano-dispersion liquid after sand grinding is 50nm. The gas used to atomize the yttrium oxide nano-dispersion liquid is air, and the air flow rate is 35L / min. The lithium nickel manganese oxide positive electrode material is in a flowing state by passing hot air into the fluidized bed. The temperature of the hot air is 115°C, and the air intake of the hot air is 0.35m 3 / min. The heating rate during the sintering process was 3℃ / min, and the temperature was raised to 500℃ and kept for 8h. The sintering was carried out in an air atmosphere. The thickness of the obtained coating layer was about 15nm.

[0068] Example 2

[0069] The difference between this embodiment and embodiment 1 is that the amount of the yttrium oxide nano-dispersion liquid dispersed by sand milling is 100 g.

[0070] Example 3

[0071] The difference between this embodiment and embodiment 1 is that the coating agent is tantalum oxide.

[0072] Example 4

[0073] The difference between this embodiment and embodiment 1 is that the coating agent is tungsten oxide.

[0074] Example 5

[0075] This embodiment provides a modified lithium nickel manganese oxide positive electrode material, and the preparation method thereof includes:

[0076] S1: preparing lithium nickel manganese oxide positive electrode material.

[0077] 1 kg of Ni 0.25 Mn 0.75 The (OH)2 precursor is mixed with lithium carbonate and dopants (SrCO3, Sb2O3 and Nb2O5) and then calcined to obtain the lithium nickel manganese oxide positive electrode material Li 0.5 Ni 0.25 Mn0.75 O2, after crushing, pass through 400 mesh sieve for later use.

[0078] The ratio of the molar amount of Li in lithium carbonate to the total molar amount of Ni and Mn in the lithium nickel manganese oxide positive electrode material precursor is 0.5:1. The amount of SrCO3, Sb2O3 and Nb2O5 is 0.1wt% of the lithium nickel manganese oxide positive electrode material precursor. The heating rate during the calcination process is 3°C / min, and the temperature is raised to 900°C and kept for 15 hours. The calcination is carried out in an air atmosphere.

[0079] S2: coating the lithium nickel manganese oxide positive electrode material.

[0080] 500 g of yttrium oxide nano-dispersion dispersed by sand milling was sprayed into the fluidized bed by air flow atomization, mixed with 1 kg of lithium nickel manganese oxide positive electrode material in a flowing state in the fluidized bed, and sintered to obtain a modified lithium nickel manganese oxide positive electrode material.

[0081] The concentration of the yttrium oxide nano-dispersion liquid is 10wt%, and the particle size of the yttrium oxide in the yttrium oxide nano-dispersion liquid after sand grinding is 100nm. The gas used to atomize the yttrium oxide nano-dispersion liquid is air, and the air flow rate is 50L / min. The lithium nickel manganese oxide positive electrode material is in a flowing state by passing hot air into the fluidized bed, the temperature of the hot air is 100°C, and the air intake of the hot air is 0.5m 3 / min. The heating rate during the sintering process was 3℃ / min, and the temperature was raised to 650℃ and kept for 10h. The sintering was carried out in an air atmosphere. The thickness of the obtained coating layer was about 16nm.

[0082] Example 6

[0083] This embodiment provides a modified lithium nickel manganese oxide positive electrode material, and the preparation method thereof includes:

[0084] S1: preparing lithium nickel manganese oxide positive electrode material.

[0085] 1 kg of Ni 0.25 Mn 0.75 The (OH)2 precursor is mixed with lithium carbonate and dopants (SrCO3, Sb2O3 and Nb2O5) and then calcined to obtain the lithium nickel manganese oxide positive electrode material Li 0.5 Ni 0.25 Mn 0.75 O2, after crushing, pass through 400 mesh sieve for later use.

[0086] The ratio of the molar amount of Li in lithium carbonate to the total molar amount of Ni and Mn in the lithium nickel manganese oxide positive electrode material precursor is 0.55:1. The amount of SrCO3, Sb2O3 and Nb2O5 is 2wt% of the lithium nickel manganese oxide positive electrode material precursor. The heating rate during the calcination process is 3°C / min, and the temperature is raised to 1100°C and kept for 8 hours. The calcination is carried out in an air atmosphere.

[0087] S2: coating the lithium nickel manganese oxide positive electrode material.

[0088] 500 g of yttrium oxide nano-dispersion dispersed by sand milling was sprayed into the fluidized bed by air flow atomization, mixed with 1 kg of lithium nickel manganese oxide positive electrode material in a flowing state in the fluidized bed, and sintered to obtain a modified lithium nickel manganese oxide positive electrode material.

[0089] The concentration of the yttrium oxide nano-dispersion liquid is 10wt%, and the particle size of the yttrium oxide in the yttrium oxide nano-dispersion liquid after sand grinding and dispersion is 20nm. The gas used to atomize the yttrium oxide nano-dispersion liquid is air, and the air flow rate is 20L / min. The lithium nickel manganese oxide positive electrode material is in a flowing state by passing hot air into the fluidized bed. The temperature of the hot air is 130°C, and the air intake of the hot air is 0.2m 3 / min. The heating rate during the sintering process was 3℃ / min, and the temperature was raised to 800℃ and kept for 6h. The sintering was carried out in an air atmosphere. The thickness of the obtained coating layer was about 14nm.

[0090] Comparative Example 1

[0091] The difference between this comparative example and Example 1 is that in S2, the material mixing method is replaced by mechanical mixing, and the yttrium oxide nano-dispersion liquid is replaced by 50 g of nano-yttrium oxide powder.

[0092] Comparative Example 2

[0093] The difference between this comparative example and Example 3 is that in S2, the material mixing method is replaced by mechanical mixing, and the tantalum oxide nano-dispersion liquid is replaced by 50 g of nano-tantalum oxide powder.

[0094] Comparative Example 3

[0095] The difference between this comparative example and Example 1 is that in S2, the amount of the yttrium oxide nano-dispersion liquid dispersed by sand milling is 50 g.

[0096] Comparative Example 4

[0097] The difference between this comparative example and Example 1 is that in S2, the amount of the yttrium oxide nano-dispersion liquid dispersed by sand milling is 2000 g.

[0098] Comparative Example 5

[0099] The difference between this comparative example and Example 1 is that in S2, in the yttrium oxide nano-dispersion liquid dispersed by sand milling, the particle size of yttrium oxide is 150 nm.

[0100] Comparative Example 6

[0101] The difference between this comparative example and Example 1 is that in S2, the amount of yttrium oxide used is 15wt% of the lithium nickel manganese oxide positive electrode material.

[0102] Comparative Example 7

[0103] The difference between this comparative example and Example 1 is that in S2, the flow rate of the air for atomizing the nano-dispersion of the coating agent is 10 L / min.

[0104] Comparative Example 8

[0105] The difference between this comparative example and Example 1 is that in S2, the flow rate of the air for atomizing the coating agent nano-dispersion liquid is 60 L / min.

[0106] Comparative Example 9

[0107] The difference between this comparative example and Example 1 is that in S2, the temperature of the air that makes the lithium nickel manganese oxide positive electrode material flow is room temperature (about 25° C.).

[0108] Comparative Example 10

[0109] The difference between this comparative example and Example 1 is that in S2, the intake volume of the hot air that makes the nickel manganese oxide positive electrode material flow is 0.1m 3 / min.

[0110] Test example

[0111] ①, taking Examples 1 to 2 and Comparative Example 1 as examples, the obtained modified lithium nickel manganese oxide positive electrode materials were observed by scanning electron microscope, and the SEM images were as follows: Figures 1 to 3 shown.

[0112] Depend on Figures 1 to 3 It can be seen that compared with the island-shaped thick coating during mechanical blending, the use of a fluidized bed to assist in coating the coating agent nano-dispersion can make the coating agent as a whole tightly, firmly and continuously coated on the surface of the lithium nickel manganese oxide positive electrode material, thereby playing a barrier role on the surface of the lithium nickel manganese oxide positive electrode material, preventing it from directly contacting the electrolyte.

[0113] ②, taking Examples 1 to 2 and Comparative Examples 1 and 3 as examples, the obtained modified lithium nickel manganese oxide positive electrode material and the substrate (lithium nickel manganese oxide positive electrode material) were subjected to XPS (X-ray photoelectron spectroscopy) test to test the Mn element content on the surface of the material. The results are as follows: Figure 4 shown.

[0114] Figure 4The left starting position is taken as the standard, and from top to bottom, they correspond to the substrate, Example 1, Example 2, Comparative Example 1 and Comparative Example 3.

[0115] Figure 4 The larger the peak area, the higher the Mn content on the surface of the test material. The test depth is about 10nm. Figure 4 It can be seen that the surface of the modified lithium nickel manganese oxide positive electrode material obtained in Examples 1 to 2 is almost undetectable for the Mn element unique to the substrate (lithium nickel manganese oxide positive electrode material), indicating that the coating effect is dense and continuous, and the coating layer completely covers the positive electrode surface; while the conventional mechanical blending method of Comparative Example 1 is consistent with the test results of the substrate (lithium nickel manganese oxide positive electrode material), indicating that the mechanical blending method cannot achieve the effect of continuous full coating. In Comparative Example 3, too little coating agent is used, which will also lead to a significant deterioration in the coating effect.

[0116] ③. The modified lithium nickel manganese oxide positive electrode materials obtained in Examples 1 to 6 and Comparative Examples 1 to 10 were prepared into 2025 button batteries and electrochemical performance tests were performed. The preparation and testing methods are as follows:

[0117] The prepared materials include: ternary positive electrode: carbon black: PVDF = 90:5:5, the negative electrode is metallic lithium, and the electrolyte is Xinzhoubang (M10).

[0118] The test conditions include: the charge and discharge voltage range is 3.5V to 4.95V, and after charging and discharging once at different rates (0.1C, 0.2C, 0.5C, 1C), the 1C capacity and cycle performance are finally tested at room temperature. The results are shown in Table 1.

[0119] Table 1 Test results

[0120]

[0121]

[0122] It can be seen from Table 1 that the modified lithium nickel manganese oxide positive electrode materials obtained in Examples 1 to 6 are more conducive to improving the battery's withholding capacity and cycle retention rate than the modified lithium nickel manganese oxide positive electrode materials obtained in Comparative Examples 1 to 10.

[0123] In summary, the preparation method provided by the present invention can form a uniform, continuous, dense and thick coating layer on the surface of the lithium nickel manganese oxide positive electrode material, reduce the direct contact between the surface of the lithium nickel manganese oxide positive electrode material and the electrolyte, and slow down the Mn 3+ dissolution, which is beneficial to improve the capacity and cycle performance of the battery.

[0124] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a modified lithium nickel manganese oxide positive electrode material, characterized in that: The following steps are involved: The coating agent nano-dispersion liquid dispersed by sand milling is sprayed into a fluidized bed by air flow atomization, mixed with the lithium nickel manganese oxide positive electrode material in a flowing state in the fluidized bed, and sintered to obtain a modified lithium nickel manganese oxide positive electrode material containing a coating layer; The particle size of the coating agent in the coating agent nano-dispersion liquid is not more than 100 nm; the amount of the coating agent is not more than 10 wt% of the lithium nickel manganese oxide positive electrode material; the thickness of the coating layer is not less than 10 nm; The gas used to atomize the coating agent nano-dispersion liquid is air, and the flow rate of the air is 20L / min to 50L / min; hot air is introduced into the fluidized bed to make the lithium nickel manganese oxide positive electrode material flow; the temperature of the hot air is 100°C to 130°C; the air intake volume of the hot air is 0.2m 3 / min~0.5m 3 / min.

2. The preparation method according to claim 1, characterized in that: The thickness of the coating layer is 10nm to 20nm; Alternatively, the amount of the coating agent used is 1wt% to 5wt% of the lithium nickel manganese oxide positive electrode material.

3. The preparation method according to claim 1 or 2, characterized in that: The coating agent includes at least one of yttrium oxide, tungsten oxide and tantalum oxide.

4. The preparation method according to claim 1 or 2, characterized in that: The concentration of the coating agent in the coating agent nano-dispersion liquid does not exceed 10 wt %.

5. The preparation method according to claim 1 or 2, characterized in that: The sintering temperature is 500°C to 800°C, and the sintering time is 6h to 10h.

6. The preparation method according to claim 1, characterized in that: The preparation of the lithium nickel manganese oxide positive electrode material comprises: mixing a lithium nickel manganese oxide positive electrode material precursor with a lithium source and then calcining; The chemical formula of the lithium nickel manganese oxide positive electrode material precursor is Ni x Mn y (OH)2, 0.2≤x≤0.3, y=1-x; The lithium source includes lithium carbonate; The ratio of the molar amount of Li in the lithium source to the total molar amount of Ni and Mn in the lithium nickel manganese oxide positive electrode material precursor is 0.5:1 to 0.55:

1.

7. The preparation method according to claim 6, characterized in that: Mixing the lithium nickel manganese oxide positive electrode material precursor with the lithium source and the dopant and then calcining; Wherein, the dopant includes at least one of SrCO3, Sb2O3 and Nb2O5, and the amount of each dopant is 0.1wt% to 2wt% of the lithium nickel manganese oxide positive electrode material precursor.

8. The preparation method according to claim 6 or 7, characterized in that: The calcination temperature is 900°C to 1100°C, and the calcination time is 8h to 15h.

9. A modified lithium nickel manganese oxide positive electrode material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.

10. A battery, characterized in that: The raw materials for preparing the battery include the modified lithium nickel manganese oxide positive electrode material as described in claim 9.

Citation Information

Patent Citations

  • Coating method of nickel cobalt lithium manganate ternary positive electrode material

    CN111769273A

  • Lithium nickel manganese oxide positive electrode material as well as preparation method and application thereof

    CN114349074A

  • Preparation method of cobalt-free lithium ion battery positive electrode material

    CN115440941A

  • High-nickel cobalt-free positive electrode material and preparation method thereof

    CN116789187A

  • Lithium nickel manganese oxide positive electrode material as well as preparation method and application thereof

    CN119725476A